The effects of employer knowledge and product awareness of job seekers' application decision - Low, Evelyn Sze Zen *; Woo, Pei Jun * (Sunway University College, 2009)
This present study attempts to discover the relational influence of product awareness and employer knowledge to give insight to job seekers? application decisions. Cable and Turban?s (2001) employer knowledge framework was proposed as a conceptual model to formulate hypotheses about the effects of employer familiarity, employer reputation and job information on job seekers? decision to pursue or accept an employment offer. The results suggested that product awareness and the three dimensions of employer knowledge significantly contributed to applicants? job pursuit decisions. The findings of this study were derived from a sample of 280 final-year pursuants of hospitality and tourism courses at four tertiary schools located in the Klang Valley. As a further measure to verify the employer knowledge model, it was discovered that the relationship between job seekers? employment decisions and job information were particularly high. Findings gathered from this context indicated that the framework of employer knowledge warrants further investigation.